Knocking down tumor suppressor gene PTPRG enhances axonal regeneration of dorsal root ganglion neurons - Zhao, Qian; Zhang, Lan; Yang, Peng; Li, Jingjing; Yi, Sheng (Frontiers in Cell and Developmental Biology, 2025)
IntroductionNerve injuries severely impair quality of life, with the limited axonal regenerative capacity in mammals hindering functional recovery. Dorsal root ganglion (DRG) neurons serve as an essential model for the identification of axonal regeneration regulators as their peripheral axonal branches are regeneration permissive after axotomy while their central axonal branches are regeneration incompetent.MethodsIn this study, we analyze transcriptional profiling of rat DRGs in response to peripheral and central axonal injuries. We use siRNA-mediated silencing of the tumor suppressor gene PTPRG (protein tyrosine phosphatase receptor type G) in cultured DRG neurons and explants to assess its role in neurite outgrowth and axonal regeneration. RNA sequencing is used to identify associated pathways and gene expression changes.ResultsWe find that the expression of PTPRG is reduced after injury to peripheral axonal branches but increased after injury to central axonal branches. In cultured DRG neurons and DRG explants, siRNA-mediated silencing of PTPRG leads to boosted neurite outgrowth and enhanced sensory axonal regeneration. Sequencing data show that PTPRG knockdown is associated with the activation of metabolism-related pathways and altered expression of the transcription factor-coding gene prospero-related homeobox 1 (PROX1).DiscussionThese findings identify PTPRG as a novel negative regulator of axonal regeneration, expanding the repertoire of molecules that can be manipulated to improve functional recovery after nerve injuries.